2001
DOI: 10.1177/014920630102700205
|View full text |Cite
|
Sign up to set email alerts
|

Organizational identification among virtual workers: the role of need for affiliation and perceived work-based social support

Abstract: Organizational identification, which reflects how individuals define the self with respect to their organization, may be called into question in the context of virtual work. Virtual work increases employees’ isolation and independence, threatening to fragment the organization. This study finds that virtual workers’ need for affiliation and the work-based social support they experience are countervailing forces associated with stronger organizational identification. Furthermore, perceived work-based social supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(205 citation statements)
references
References 26 publications
5
179
0
3
Order By: Relevance
“…They also found several individual factors with positive relationships, such as tenure, satisfaction with the organization, and sentimentality. Other potential antecedents include person-organization fit (O'Reilly & Chartman, 1986), job satisfaction (Wiesenfeld et al, 2001), employee communication (Smidts et al, 2001), need to identify, and positive affectivity (Kreiner & Ashford, 2004).…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 99%
“…They also found several individual factors with positive relationships, such as tenure, satisfaction with the organization, and sentimentality. Other potential antecedents include person-organization fit (O'Reilly & Chartman, 1986), job satisfaction (Wiesenfeld et al, 2001), employee communication (Smidts et al, 2001), need to identify, and positive affectivity (Kreiner & Ashford, 2004).…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 99%
“…Among these works, most have started to incorporate insights from social exchange theory to explain the development of OID. For example, Wiesenfeld, Raghuram and Garud (2001) found that perceived work-based social support -the degree to which individuals perceive that they have positive social relationships with others in the workplaceis positively related to OID among virtual workers. Sluss, Klimchak and Holmes (2008) found that POS mediates the effect of leader-member exchange on OID.…”
Section: Perceived Organizational Support (Pos) and Oidmentioning
confidence: 99%
“…POS is a major indicator of employees' perception of how an organization treats them (Kiewitz, Restubog, Zagenczyk and Hochwarter, 2009;Zagenczyk et al, 2010). In addition, Wiesenfeld, Raghuram and Garud (2001) argue that supportive organizational constituents (incl.…”
Section: Perceived Organizational Support (Pos) and Oidmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a relational take on organizational learning is important and timely because work is becoming more interdependent (Thompson, 1967;Wageman, 1995;Kellogg et al, 2006), as well as more complex ((e.g. work settings are becoming more virtual (see Raghuram et al, 2001;Wiesenfeld et al, 2001)). In these changing conditions, the importance of quality relationships among organizational members is increasing, while the achievement of quality relationships is more challenging.…”
Section: Introductionmentioning
confidence: 99%